If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(n + 7) = -6 Reorder the terms: 3(7 + n) = -6 (7 * 3 + n * 3) = -6 (21 + 3n) = -6 Solving 21 + 3n = -6 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-21' to each side of the equation. 21 + -21 + 3n = -6 + -21 Combine like terms: 21 + -21 = 0 0 + 3n = -6 + -21 3n = -6 + -21 Combine like terms: -6 + -21 = -27 3n = -27 Divide each side by '3'. n = -9 Simplifying n = -9
| X+x+.5x+.5x=360 | | 8t-11=5t-5 | | 15x^2-29x+120=0 | | -4(x+1)=5x+5 | | -4x^2-4x-8=0 | | 15x^2-29x+29=0 | | 4d-13+7=-24 | | 6v+28=2(v+6) | | 4x^2-4v-8=0 | | 0=-16t^2+10t+1 | | [-14+(-7)]+[-8+13]= | | 5x+9=140 | | 3x=2y^2 | | 4d-13=-24 | | 13=5-13+3 | | 36=8w+2.6-36 | | 7m=-19 | | 9v^2+23v+14=0 | | h=-16t^2+10t+1 | | 50h=60h | | -x-2y=7 | | 10x^2+36=0 | | 16-2w=10w-2-6w | | 3x-9y-8x+5y= | | -10=9k-Pr | | (-4+x)10=2x | | 625-a^4=0 | | 150+.10x=167 | | 15a-54=-89 | | 15x^2-6x=3x | | 2.5q-4.8-4.6q=-3.1q-2.7 | | X+(2A)+(B+2ft)=70 |